Method for producing water-soluble quantum dot and water-soluble quantum dot

By exchanging hydrophobic ligands with hydrophilic ones and forming shells on quantum dots, the method addresses the issue of decreased quantum yield and broadened emission spectra, resulting in high-performance water-soluble quantum dots for bioimaging.

JP2024177865APending Publication Date: 2024-12-24NIPPON CHEMICAL IND CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023096240
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing methods for making quantum dots water-soluble result in significant decreases in quantum yield and broadening of emission spectra, compromising their luminescent properties.

Method used

A method involving ligand exchange with hydrophilic ligands, followed by surface treatment and shell formation, is used to produce water-soluble quantum dots with improved quantum yield and narrow emission spectra.

Benefits of technology

The method produces quantum dots with quantum yield maintenance greater than 0.8 and FWHM equivalent to those in organic solvents, suitable for applications like bioimaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024177865000002
    Figure 2024177865000002
  • Figure 2024177865000003
    Figure 2024177865000003
  • Figure 2024177865000004
    Figure 2024177865000004
Patent Text Reader

Abstract

To provide: a method for producing a water-soluble quantum dot which is excellent in quantum yield in an aqueous solvent such as water, and can obtain a light emission spectrum having a narrow FWHM; and a water-soluble quantum dot which is obtained by the production method.SOLUTION: A method for producing a water-soluble quantum dot includes: a ligand exchange step of adding a hydrophilic ligand to a hydrophobic quantum dot dispersion liquid and exchanging a ligand bonded to the surface of a quantum dot with a hydrophilic ligand to obtain a hydrophilic quantum dot; a dispersion step of dispersing the hydrophilic quantum dot into an aqueous medium to obtain an aqueous solvent dispersion liquid of the hydrophilic quantum dot; a surface treatment step of adding a surface treatment agent to the aqueous solvent dispersion liquid, subjecting the hydrophilic quantum dot to surface treatment in the aqueous medium to obtain an aqueous solvent dispersion liquid of the surface-treated hydrophilic quantum dot; and a shell formation step of adding a shell formation agent to the aqueous solvent dispersion liquid of the surface-treated hydrophilic quantum dot and forming a shell on the surface of the surface-treated hydrophilic quantum dot to obtain an aqueous solvent dispersion liquid of the water-soluble quantum dot.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing water-soluble quantum dots and water-soluble quantum dots obtained by the method. [Background technology]

[0002] In recent years, the development of quantum dots as luminescent materials has progressed. Cadmium-based quantum dots such as CdSe, CdTe, and CdS are being developed as representative quantum dots due to their excellent luminescence properties. In addition, since cadmium is highly toxic and has a high environmental impact, the development of cadmium-free quantum dots such as InP, CuInS2, and ZnTeSe is expected.

[0003] Taking advantage of these excellent luminescence properties, a method is used to measure biological substances such as proteins, viruses, and nucleic acids using a molecular recognition body in which a molecular recognition substance is bound to a marker substance such as a fluorescent substance. In order to use quantum dots as marker substances in a living body, it is necessary to make the quantum dots water-soluble by coating the surface of the quantum dots with a water-soluble ligand.

[0004] As a method for coating the quantum dot surface with a water-soluble ligand to make the quantum dot water-soluble, for example, in the examples of Patent Document 1, it is described that InP quantum dots are contacted with zinc acetate and mercaptoacetic acid in an aqueous solvent to obtain water-soluble quantum dots of a core-shell structure of InP / ZnS modified with mercaptoacetic acid as a ligand. In addition, in the examples of Patent Document 2, water-soluble InP / ZnS core-shell quantum dots are also disclosed, and as a method for producing them, it is described that indium chloride, zinc chloride, tris(diethylamino)phosphine and sodium propanesulfonate are reacted in an amine, and then mercaptopropionic acid is added to obtain InP / ZnS core-shell quantum dots coordinated with mercaptopropionic acid, and then the InP / ZnS core-shell quantum dots are dispersed in water.

[0005] It is generally known that when quantum dots are made water-soluble, the quantum yield is significantly reduced, and the emission characteristics are deteriorated, such as the full width at half maximum (FWHM) of the emission spectrum becoming wider. This is thought to be because defects are generated on the quantum dot surface due to the ligand exchange during water-solubilization. In the above patent document, there is a concern that the emission characteristics will be reduced because defects are generated on the quantum dot surface when the ligand for water-solubilization is exchanged with a compound having a mercapto group.

[0006] To address this issue, Patent Document 3 describes that in order to obtain water-soluble quantum dots with high brightness and stability, after ligand exchange with mercaptopropionic acid, a mixed aqueous solution of zinc chloride and mercaptopropionic acid is added, thereby growing a ZnS shell layer while protecting defects on the quantum dot surface with zinc, thereby improving the luminescence characteristics. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] China Patent Application Publication No. 102031111 [Patent Document 2] China Patent Application Publication No. 114136934 [Patent Document 3] China Patent Application Publication No. 114891508 Summary of the Invention [Problem to be solved by the invention]

[0008] As in Patent Document 3, by forming a shell while protecting the defects on the quantum dot surface that occur during ligand exchange, it is possible to impart excellent luminescence properties even in water. However, it is difficult to achieve luminescence properties equal to or better than those in organic solvents, and further investigation is required.

[0009] Therefore, an object of the present invention is to provide a method for producing water-soluble quantum dots that have excellent quantum yield in an aqueous solvent such as water and can provide an emission spectrum with a narrow FWHM, and to provide water-soluble quantum dots obtained by the method. [Means for solving the problem]

[0010] As a result of intensive research to solve the above problems, the inventors have found that if ligand-exchanged quantum dots are surface-treated in an aqueous solvent to repair defects on the quantum dot surface, and then a shell is formed, even water-soluble quantum dots have an FWHM equivalent to that of quantum dots obtained in an organic solvent, and the decrease in quantum yield is also suppressed, thereby completing the present invention.

[0011] That is, the present invention provides a method for producing water-soluble quantum dots, comprising: a ligand exchange step of adding hydrophilic ligands to a hydrophobic quantum dot dispersion and exchanging the ligands bonded to the surfaces of the quantum dots for hydrophilic ligands to obtain hydrophilic quantum dots; a dispersion step of dispersing the hydrophilic quantum dots in an aqueous solvent to obtain an aqueous solvent dispersion of hydrophilic quantum dots; a surface treatment step of adding a surface treatment agent to the aqueous solvent dispersion to perform surface treatment of the hydrophilic quantum dots in the aqueous solvent to obtain an aqueous solvent dispersion of surface-treated hydrophilic quantum dots; and a shell formation step of adding a shell forming agent to the aqueous solvent dispersion of the surface-treated hydrophilic quantum dots to form a shell on the surface of the surface-treated hydrophilic quantum dots to obtain an aqueous solvent dispersion of water-soluble quantum dots.

[0012] The present invention also provides water-soluble quantum dots, in which the quantum yield of the water-soluble quantum dots obtained by exchanging the ligands bound to the surface of the hydrophobic quantum dots with hydrophilic ligands is greater than 0.8 relative to the quantum yield of the hydrophobic quantum dots. Effect of the Invention

[0013] According to the present invention, water-soluble quantum dots that have excellent quantum yield in an aqueous solvent and can provide an emission spectrum with a narrow FWHM can be produced by an industrially advantageous method. [Brief description of the drawings]

[0014] [Figure 1] 1 shows an emission spectrum of the water dispersion of water-soluble quantum dots obtained in Example 1. [Diagram 2] 1 is an emission spectrum of the water dispersion of water-soluble quantum dots obtained in Example 2. [Diagram 3] 1 shows an emission spectrum of the water dispersion of water-soluble quantum dots obtained in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] <Hydrophobic quantum dot dispersion> The hydrophobic quantum dot dispersion liquid used in the present invention is a liquid in which hydrophobic quantum dots are dispersed in a solvent, and the hydrophobic quantum dots are quantum dots having hydrophobic ligands on their surfaces. The hydrophobic quantum dot dispersion liquid may be one obtained by reacting raw material compounds consisting of elements constituting the hydrophobic quantum dots in a solvent, or may be one obtained by dispersing commercially available hydrophobic quantum dots in a solvent.

[0016] The solvent of the dispersion liquid is preferably a non-polar organic solvent, more preferably a solvent made of an aliphatic hydrocarbon. Examples of the aliphatic hydrocarbon include saturated hydrocarbons such as n-hexane, n-heptane, n-octane, n-nonane, n-decane, n-dodecane, n-hexadecane, and n-octadecane; and unsaturated aliphatic hydrocarbons such as 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-octadecene. The aliphatic hydrocarbon used as the solvent may be one type, or two or more types may be mixed together.

[0017] Examples of the quantum dots constituting the hydrophobic quantum dots include cadmium-based quantum dots such as CdSe, CdTe, and CdS, and cadmium-free quantum dots such as InP, CuInS, and ZnTeSe. In the present invention, the quantum dots are preferably of a core-shell structure in which a shell is formed on the surface of a core, and are particularly preferably of a core-shell structure in which the core has at least an InP-based quantum dot obtained by reacting a phosphorus source with an indium source, and the shell has a coating compound other than an InP-based compound.

[0018] Examples of the hydrophobic ligand that constitutes the hydrophobic quantum dots include carboxylic acid derivatives, phosphine derivatives, amine derivatives, and phosphonic acid.

[0019] The carboxylic acid derivative is preferably one in which the alkyl group in the molecule is linear and has 2 to 24 carbon atoms. Specific examples of carboxylic acids in which the alkyl group in the molecule is linear and has 2 to 24 carbon atoms include capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, elaidic acid, oleic acid, linolenic acid, and erucic acid. Among these, from the viewpoint of improving the quality of the obtained hydrophobic quantum dots, those in which the alkyl group in the molecule has 12 to 20 carbon atoms are particularly preferred, and oleic acid is the most preferred.

[0020] The phosphine derivative is preferably a primary to tertiary alkylphosphine, and the alkyl group in the molecule is preferably a straight chain having 2 to 18 carbon atoms. The alkyl groups in the molecule may be the same or different. Specific examples of the alkyl phosphine having a straight chain alkyl group having 2 to 18 carbon atoms include monoethylphosphine, monobutylphosphine, monodecylphosphine, monohexylphosphine, monooctylphosphine, monododecylphosphine, monohexadecylphosphine, diethylphosphine, dibutylphosphine, didecylphosphine, dihexylphosphine, dioctylphosphine, didodecylphosphine, dihexadecylphosphine, triethylphosphine, tributylphosphine, tridecylphosphine, trihexylphosphine, trioctylphosphine, tridodecylphosphine, and trihexadecylphosphine. Among these, from the viewpoint of improving the quality of the obtained hydrophobic quantum dots, those in which the number of carbon atoms in the alkyl group in the molecule is 4 to 12 are particularly preferred, those which are trialkylphosphines are preferred, and trioctylphosphine is most preferred.

[0021] The amine derivative is preferably a primary to tertiary alkylamine, and preferred examples thereof include linear alkylamines in which the alkyl group in the molecule has 2 to 18 carbon atoms, and aromatic alkylamines in which the alkyl group has 6 to 12 carbon atoms. The alkyl groups in the molecule may be the same or different. Specific examples of linear alkylamines in which the alkyl group has 2 to 18 carbon atoms include monoethylamine, monobutylamine, monodecylamine, monohexylamine, monooctylamine, monododecylamine, monohexadecylamine, diethylamine, dibutylamine, didecylamine, dihexylamine, dioctylamine, didodecylamine, dihexadecylamine, triethylamine, tributylamine, tridecylamine, trihexylamine, trioctylamine, tridodecylamine, and trihexadecylamine. Specific examples of aromatic alkylamines in which the alkyl group has 6 to 12 carbon atoms include aniline, diphenylamine, triphenylamine, monobenzylamine, dibenzylamine, tribenzylamine, naphthylamine, dinaphthylamine, and trinaphthylamine. The phosphonic acid is preferably a monoalkylphosphonic acid in which the alkyl group in the molecule is a straight-chain alkyl group having from 2 to 18 carbon atoms.

[0022] When the hydrophobic quantum dots used in the present invention have a core-shell structure, examples of coating compounds suitable for the shell include AlN, AlP, Al2O3, GaN, GaP, Ga2O3, SiO2, CdS, CdSe, CdSeS, CdTe, CdSeTe, CdTeS, ZnS, ZnSe, ZnSeS, ZnTe, ZnSeTe, ZnTeS, ZnO, ZnOS, ZnSeO, and ZnTeO, etc. In the present invention, it is preferable that the coating compound is obtained by reaction with at least a zinc source.

[0023] The hydrophobic quantum dot dispersion used in the present invention can be produced by a known method, for example, the method described in JP-A-2023-033157.

[0024] <Ligand exchange process> The ligand exchange reaction in the present invention is a process in which hydrophilic ligands are added to a hydrophobic quantum dot dispersion liquid, and the ligands bonded to the surface of the quantum dots are exchanged for hydrophilic ligands to obtain hydrophilic quantum dots.

[0025] Examples of hydrophilic ligands include thiols, amine-containing thiols, amines, alcohols, thiol-containing alcohols, selenols, phosphites, phosphinic acids, phosphonic acids, phosphoric acids, phosphine oxides, phosphine sulfides, phosphine selenides, carboxylic acids, thiol-containing carboxylic acids, thiocarboxylic acids, thionocarboxylic acids, dithiocarboxylic acids, sulfenic acids, sulfinic acids, and sulfonic acids. Among these, thiols, amine-containing thiols, amines, alcohols, thiol-containing alcohols, phosphonic acids, carboxylic acids, and thiol-containing carboxylic acids are preferred from the viewpoint of stability and quantum yield improvement of hydrophilic quantum dots, and thiol-containing carboxylic acids are particularly preferred.

[0026] Examples of the thiol-containing carboxylic acid include thioglycolic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, thiomalic acid, cysteine, acetylcysteine, homocysteine, penicillamine, etc. Among these, from the viewpoint of improving the water dispersibility and quantum yield of the quantum dots, thioglycolic acid, 3-mercaptopropionic acid, cysteine, and acetylcysteine ​​are preferred, and 3-mercaptopropionic acid is more preferred.

[0027] The temperature when adding hydrophilic ligands to the quantum dot dispersion is preferably 0°C to 350°C, more preferably 20°C to 300°C, and the treatment time is preferably 1 minute to 600 minutes, more preferably 5 minutes to 240 minutes. The amount of the ligand to be added depends on the type of the ligand, but is preferably 0.01 g / L to 100,000 g / L, more preferably 0.1 g / L to 2,000 g / L, relative to the reaction solution containing the quantum dots.

[0028] The atmosphere when adding the hydrophilic ligand to the quantum dot dispersion liquid is preferably a non-oxidizing atmosphere such as an inert gas atmosphere, reduced pressure, or vacuum, from the viewpoint of preventing the denaturation of the quantum dots and the by-production of oxides. From the viewpoint of ease of operation, the non-oxidizing atmosphere is preferably an inert gas atmosphere such as nitrogen gas or argon gas. Through the above steps, a dispersion liquid containing hydrophilic quantum dots is obtained.

[0029] Next, the hydrophilic quantum dots are separated from the dispersion liquid containing the hydrophilic quantum dots. Examples of the separation method include common methods such as centrifugation, decantation, and suction filtration. At this time, in order to remove unnecessary hydrophobic ligands, it is preferable to add a solvent capable of dissolving the ligands and repeat the operation of separating the hydrophilic quantum dots by centrifugation or the like several times. Through the above steps, hydrophilic quantum dots are obtained.

[0030] <Dispersion process> The dispersion step in the present invention is a step of dispersing the hydrophilic quantum dots in an aqueous solvent to obtain an aqueous solvent dispersion of the hydrophilic quantum dots.

[0031] The aqueous solvent is not particularly limited as long as it is a water-soluble solvent, and examples thereof include water, methanol, ethanol, 2-propanol, ethylene glycol, propylene glycol, acetone, acetonitrile, N-methylpyrrolidone, dimethylformamide, and tetrahydrofuran, with water being preferred.

[0032] The hydrophilic quantum dot aqueous solvent dispersion is obtained by dispersing the hydrophilic quantum dots in the aqueous solvent. The hydrophilic quantum dots can be dispersed in the aqueous solvent as they are, but for example, when the hydrophilic ligand is a carboxylic acid containing a thiol, it is preferable to react these with ammonia water or tetraethylammonium hydroxide, etc., to convert them into the form of an ammonium salt, and then disperse them in the aqueous solvent, from the viewpoint of obtaining a uniform dispersion.

[0033] In addition, since the hydrophilic quantum dots before the dispersion process may contain by-products or unreacted impurities, they may be subjected to a purification process. This purification process can be performed by adding an organic solvent such as methanol, ethanol, 2-propanol, acetone, acetonitrile, or tetrahydrofuran to a solution containing hydrophilic quantum dots to precipitate the hydrophilic quantum dots, separating the solution containing impurities from the hydrophilic quantum dots, and dispersing the separated hydrophilic quantum dots in an aqueous solvent. The solution containing impurities and the hydrophilic quantum dots can be separated by operations such as centrifugation, decantation, and suction filtration. Through the above steps, an aqueous solvent dispersion of hydrophilic quantum dots is obtained.

[0034] <Surface treatment process> The surface treatment step in the present invention is a step of adding a surface treatment agent to the aqueous solvent dispersion to perform surface treatment of the hydrophilic quantum dots in an aqueous solvent, thereby obtaining an aqueous solvent dispersion of the surface-treated hydrophilic quantum dots.

[0035] In the surface treatment step, defects on the quantum dot surface caused by the ligand exchange step are repaired in an aqueous solvent with a surface treatment agent, so that the quantum dots become stable and the surface becomes uniform, enabling stable shell formation in the shell formation step described below. Therefore, the water-soluble quantum dots finally obtained according to the present invention have the same FWHM as the quantum dots obtained in an organic solvent, and the decrease in quantum yield is suppressed.

[0036] Examples of the surface treatment agent include metal halides such as halides of Li, Na, K, Be, Mg, Ca, Sr, Cu, Ag, Au, Hg, In, Sn, Pb, Zn, Cd, Al, and Ga; hydrogen halides such as HF, HCl, HBr, and HI; nitrogen halides such as NF3; halides of quaternary ammonium compounds and quaternary phosphonium compounds such as NR4F and PR4F (R represents H, or a saturated, unsaturated, or aromatic hydrocarbon having 1 to 8 carbon atoms which may be linear or branched, and which may be substituted with a functional group); carboxylic acids, phosphonic acids, sulfonic acids, and acid halides thereof; and metal carboxylates, metal carbamates, and metal thiocarboxylates containing metals such as Li, Na, K, Be, Mg, Ca, Sr, Cu, Ag, Au, Hg, In, Sn, Pb, Zn, Cd, Al, and Ga. Among these, from the viewpoint of further improving the quantum yield, the surface treatment agent is preferably a metal halide or a metal carboxylate. The metal halide may be zinc fluoride, zinc chloride, zinc bromide, zinc iodide, etc., and zinc chloride is particularly preferred. The metal carboxylate may be zinc acetate, zinc trifluoroacetate, zinc myristate, zinc oleate, zinc benzoate, etc., and zinc acetate is particularly preferred.

[0037] The surface treatment of the hydrophilic quantum dots can be carried out by adding a surface treatment agent to the hydrophilic quantum dot aqueous solvent dispersion. The surface treatment is preferably carried out at a temperature of -20°C or higher and 200°C or lower, more preferably at a temperature of 0°C or higher and 150°C or lower, particularly at a temperature of 20°C or higher and 120°C or lower, and preferably for 1 minute or longer and 600 minutes or shorter, more preferably at a temperature of 5 minutes or longer and 240 minutes or shorter, particularly at a temperature of 10 minutes or longer and 120 minutes or shorter. The amount of the surface treatment agent added depends on the type of the surface treatment agent, but is preferably 0.01 g / L or higher and 10,000 g / L or lower, more preferably 0.1 g / L or higher and 1,000 g / L or lower, relative to the hydrophilic quantum dot aqueous solvent dispersion.

[0038] The atmosphere in the surface treatment step is preferably a non-oxidizing atmosphere such as an inert gas atmosphere, reduced pressure, or vacuum, from the viewpoint of preventing the denaturation of the quantum dots and the by-production of oxides. From the viewpoint of ease of operation, the non-oxidizing atmosphere is preferably an inert gas atmosphere such as nitrogen gas or argon gas.

[0039] The method of adding the surface treatment agent in the surface treatment step includes a method of directly adding the surface treatment agent to the reaction liquid, and a method of adding the surface treatment agent dissolved or dispersed in a solvent to the reaction liquid. When the surface treatment agent is added by a method of adding the surface treatment agent dissolved or dispersed in a solvent to the reaction liquid, the solvent is not particularly limited as long as it is a water-soluble solvent, and examples of the solvent include water, methanol, ethanol, 2-propanol, ethylene glycol, propylene glycol, acetone, acetonitrile, N-methylpyrrolidone, dimethylformamide, and tetrahydrofuran, with water being particularly preferred. Through the above steps, an aqueous solvent dispersion of surface-treated hydrophilic quantum dots is obtained.

[0040] <Shell formation process> The shell formation step in the present invention is a step of adding a shell forming agent to the aqueous solvent dispersion of the surface-treated hydrophilic quantum dots to form a shell on the surface of the surface-treated hydrophilic quantum dots, thereby obtaining an aqueous solvent dispersion of water-soluble quantum dots.

[0041] The shell-forming agent is preferably a mixture of at least one sulfur source selected from thiols, thiol-containing carboxylic acids, thioureas, thiocarbamates, thiocarbonates, thiocarboxylic acids, thionocarboxylic acids, dithiocarboxylic acids, phosphine sulfides, and sulfides of Li, Na, K, Be, Mg, Ca, and Sr, and zinc carboxylate, zinc nitrate, zinc sulfate, zinc hypochlorite, zinc chlorite, zinc chlorate, zinc perchlorate, zinc bromate, zinc iodate, zinc carbonate, zinc borate, zinc hypophosphite, zinc phosphite, zinc phosphate, zinc trifluoromethanesulfonate, or zinc halide. In particular, from the viewpoint of improving the quantum yield, it is preferable to use a mixture of thiol-containing carboxylic acids as the sulfur source and zinc carboxylate, zinc perchlorate, or zinc halide as the zinc source, and it is particularly preferable to use a mixture of thiol-containing carboxylic acids and zinc halide.

[0042] Examples of the thiol-containing carboxylic acids include thioglycolic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, thiomalic acid, cysteine, acetylcysteine, homocysteine, penicillamine, etc. Among these, from the viewpoints of the water dispersibility and quantum yield of the quantum dots, thioglycolic acid, 3-mercaptopropionic acid, cysteine, and acetylcysteine ​​are preferred, and 3-mercaptopropionic acid is more preferred.

[0043] As the zinc halide, zinc fluoride, zinc chloride, zinc bromide and zinc iodide are preferred, and zinc chloride is particularly preferred.

[0044] The shell can be formed by adding a shell-forming agent to the aqueous solvent dispersion of the surface-treated hydrophilic quantum dots. After adding the shell-forming agent, the surface-treated hydrophilic quantum dots are treated at preferably 30° C. to 200° C., more preferably 50° C. to 150° C., particularly 70° C. to 120° C., for preferably 1 minute to 600 minutes, more preferably 5 minutes to 240 minutes, particularly 10 minutes to 120 minutes, to form a shell on the surface of the surface-treated hydrophilic quantum dots.

[0045] The atmosphere in the shell formation step is preferably a non-oxidizing atmosphere such as an inert gas atmosphere, reduced pressure, or vacuum, from the viewpoint of preventing the denaturation of the quantum dots and the by-production of oxides. From the viewpoint of ease of operation, the non-oxidizing atmosphere is preferably an inert gas atmosphere such as nitrogen gas or argon gas.

[0046] The method of adding the shell-forming agent in the shell-forming step includes a method of directly adding the shell-forming agent to the reaction liquid, and a method of adding the shell-forming agent dissolved or dispersed in a solvent to the reaction liquid. When the shell-forming agent is added by a method of adding the shell-forming agent dissolved or dispersed in a solvent to the reaction liquid, the solvent is not particularly limited as long as it is a water-soluble solvent, and examples of the solvent include water, methanol, ethanol, 2-propanol, ethylene glycol, propylene glycol, acetone, acetonitrile, N-methylpyrrolidone, dimethylformamide, and tetrahydrofuran, with water being particularly preferred. Through the above steps, an aqueous solvent dispersion of water-soluble quantum dots is obtained.

[0047] The water-soluble quantum dots can be separated from the obtained aqueous solvent dispersion of the water-soluble quantum dots by common methods such as centrifugation, decantation, suction filtration, etc. The obtained water-soluble quantum dots are dispersed again in an aqueous solvent to remove insoluble impurities, thereby obtaining a purified aqueous solvent dispersion of the water-soluble quantum dots.

[0048] The water-soluble quantum dots obtained by the manufacturing method of the present invention exhibit excellent luminescence properties even in an aqueous solvent, since the decrease in quantum yield from the hydrophobic quantum dots before being solubilized is suppressed. That is, when the ratio (B% / A%) of the quantum yield (B%) of the water-soluble quantum dots to the quantum yield (A%) of the quantum dots before being solubilized is taken as the quantum yield maintenance value, the maintenance value is more than 0.8, preferably 0.82 or more, so that the water-soluble quantum dots can be suitably used in fields where hydrophobic quantum dots could not be used, for example, in the field of bioimaging as a fluorescent probe. EXAMPLES

[0049] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. The properties in the examples were measured by the following methods. (1) Emission spectrum, maximum fluorescence wavelength, full width at half maximum (FWHM) and quantum yield (PLQY) The obtained aqueous dispersion of quantum dots was measured using an absolute PL quantum yield measurement device (Quantaurus-QY, manufactured by Hamamatsu Photonics KK) under measurement conditions of an excitation wavelength of 400 nm and a measurement wavelength of 200 to 950 nm. (2) Maintained quantum yield Calculated using the following formula. (Maintained quantum yield value) = (Quantum yield of water-soluble quantum dots) / (Quantum yield of quantum dots obtained in the synthesis example)

[0050] [Synthesis Example 1] Synthesis of green InP / ZnSe / ZnS quantum dots 1.04 g of indium myristate, 0.31 g of zinc myristate, and 0.06 g of indium acetate were added to 14.25 g of 1-octadecene, and the mixture was heated to 120°C under reduced pressure with stirring and degassed for 1.5 hours. After degassing, the mixture was returned to atmospheric pressure with nitrogen gas and cooled to 40°C to obtain a 1-octadecene solution of indium zinc myristate. The obtained 1-octadecene solution of indium zinc myristate was kept at 40° C. under a nitrogen atmosphere, and 2.51 g of a trioctylphosphine solution containing 10% by mass of tris(trimethylsilyl)phosphine was added thereto, and the mixture was held for 10 minutes and then naturally cooled to 20° C. As a result, a yellow liquid containing an InP quantum dot precursor was obtained. Next, the InP quantum dot precursor solution was heated to 250° C. to obtain a reaction solution of InP quantum dots. 7.54g of zinc oleate, 4.09g of zinc chloride, 5.40g of trioctylphosphine selenide, 8.90g of trioctylphosphine, 16.26g of oleylamine, and 16.26g of dioctylamine were mixed in a 200mL reaction vessel, heated to 120°C under reduced pressure with stirring, and degassed for 30 minutes. After degassing, the pressure was returned to atmospheric pressure with nitrogen gas, and the temperature was raised to 180°C under a nitrogen atmosphere, and 18.17g of the reaction solution of InP quantum dots obtained above was added, heated to 230°C and held for 30 minutes, and then further heated to 300°C and held for 60 minutes to obtain an oleylamine / dioctylamine dispersion of InP / ZnSe quantum dots having InP in the core and ZnSe in the shell. After the obtained dispersion was cooled to 240°C, 7.54 g of zinc oleate, 7.54 g of trioctylphosphine, and 4.35 g of trioctylphosphine sulfide were poured thereinto and held for 90 minutes to obtain an oleylamine / dioctylamine dispersion of multi-shell quantum dots having InP in the core and ZnSe and ZnS stacked in the shell. After cooling the obtained dispersion to room temperature, 50 g of acetone was added, the mixture was stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were suspended in 8.67 g of toluene to obtain a toluene dispersion of InP / ZnSe / ZnS quantum dots. 50 g of acetone was further added to this dispersion, the mixture was stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were suspended in 7.03 g of octane to obtain an octane dispersion of purified InP / ZnSe / ZnS quantum dots. The luminescence characteristics of the obtained dispersion were measured, and the results are shown in Table 1.

[0051] [Synthesis Example 2] Synthesis of orange InP / ZnSe / ZnS quantum dots 1.43 g of indium myristate was added to 14.25 g of 1-octadecene, and the mixture was heated to 120° C. under reduced pressure with stirring and degassed for 1.5 hours. After degassing, the mixture was returned to atmospheric pressure with nitrogen gas and cooled to 40° C. to obtain a 1-octadecene solution of indium myristate. The obtained 1-octadecene solution of indium myristate was kept at 40° C. under a nitrogen atmosphere, and 2.51 g of a trioctylphosphine solution containing 10% by mass of tris(trimethylsilyl)phosphine was added thereto, and the mixture was held for 10 minutes and then naturally cooled to 20° C. As a result, a yellow liquid containing an InP quantum dot precursor was obtained. Next, the InP quantum dot precursor solution was heated to 280° C. to obtain a reaction solution of InP quantum dots. 7.54g of zinc oleate, 4.09g of zinc chloride, 5.40g of trioctylphosphine selenide, 8.90g of trioctylphosphine, 16.26g of oleylamine, and 16.26g of dioctylamine were mixed in a 200mL reaction vessel, heated to 120°C under reduced pressure with stirring, and degassed for 30 minutes. After degassing, the pressure was returned to atmospheric pressure with nitrogen gas, and the temperature was raised to 180°C under a nitrogen atmosphere, and 18.19g of the reaction solution of InP quantum dots obtained above was added, heated to 230°C and held for 30 minutes, and then further heated to 300°C and held for 60 minutes to obtain an oleylamine / dioctylamine dispersion of InP / ZnSe quantum dots having InP in the core and ZnSe in the shell. After the obtained dispersion was cooled to 240°C, 7.54 g of zinc oleate, 7.54 g of trioctylphosphine, and 4.35 g of trioctylphosphine sulfide were poured thereinto and held for 90 minutes to obtain an oleylamine / dioctylamine dispersion of multi-shell quantum dots having InP in the core and ZnSe and ZnS stacked in the shell. After cooling the obtained dispersion to room temperature, 50 g of acetone was added, the mixture was stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were suspended in 8.67 g of toluene to obtain a toluene dispersion of InP / ZnSe / ZnS quantum dots. 50 g of acetone was further added to this dispersion, the mixture was stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were suspended in 7.03 g of octane to obtain an octane dispersion of purified InP / ZnSe / ZnS quantum dots. The luminescence characteristics of the obtained dispersion were measured, and the results are shown in Table 1.

[0052] [Synthesis Example 3] Synthesis of red InP / ZnSe / ZnS quantum dots 1.59 g of indium myristate was added to 14.25 g of 1-octadecene, and the mixture was heated to 120° C. under reduced pressure with stirring and degassed for 1.5 hours. After degassing, the mixture was returned to atmospheric pressure with nitrogen gas and cooled to 40° C. to obtain a 1-octadecene solution of indium myristate. The obtained 1-octadecene solution of indium myristate was kept at 40° C. under a nitrogen atmosphere, and 2.51 g of a trioctylphosphine solution containing 10% by mass of tris(trimethylsilyl)phosphine was added thereto, and the mixture was held for 10 minutes and then naturally cooled to 20° C. As a result, a yellow liquid containing an InP quantum dot precursor was obtained. Next, the InP quantum dot precursor solution was heated to 280° C. to obtain a reaction solution of the base InP quantum dots. In a separate reaction vessel, 2.39 g of indium myristate was added to 21.37 g of 1-octadecene, and the mixture was heated to 120°C under reduced pressure with stirring and degassed for 1.5 hours. After degassing, the mixture was returned to atmospheric pressure with nitrogen gas and cooled to 40°C to obtain a 1-octadecene solution of indium myristate. The obtained 1-octadecene solution of indium myristate was kept at 40° C. under a nitrogen atmosphere, and 3.76 g of a trioctylphosphine solution containing 10% by mass of tris(trimethylsilyl)phosphine was added thereto, and the mixture was held for 10 minutes and then naturally cooled to 20° C. As a result, a yellow liquid containing an InP quantum dot precursor was obtained. The previously prepared base InP quantum dot reaction solution was reheated to 260° C., and the newly prepared InP quantum dot precursor solution was added over 60 minutes to obtain an InP quantum dot reaction solution. 7.54g of zinc oleate, 4.09g of zinc chloride, 5.40g of trioctylphosphine selenide, 8.90g of trioctylphosphine, 16.26g of oleylamine, and 16.26g of dioctylamine were mixed in a 200mL reaction vessel, heated to 120°C under reduced pressure with stirring, and degassed for 30 minutes. After degassing, the pressure was returned to atmospheric pressure with nitrogen gas, and the temperature was raised to 180°C under a nitrogen atmosphere, and 15.29g of the reaction solution of InP quantum dots obtained above was added, heated to 230°C and held for 30 minutes, and then further heated to 300°C and held for 60 minutes to obtain an oleylamine / dioctylamine dispersion of InP / ZnSe quantum dots having InP in the core and ZnSe in the shell. After the obtained dispersion was cooled to 240°C, 7.54 g of zinc oleate, 7.54 g of trioctylphosphine, and 4.35 g of trioctylphosphine sulfide were poured thereinto and held for 90 minutes to obtain an oleylamine / dioctylamine dispersion of multi-shell quantum dots having InP in the core and ZnSe and ZnS stacked in the shell. After cooling the obtained dispersion to room temperature, 50 g of acetone was added, the mixture was stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were suspended in 8.67 g of toluene to obtain a toluene dispersion of InP / ZnSe / ZnS quantum dots. 50 g of acetone was further added to this dispersion, the mixture was stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were suspended in 7.03 g of octane to obtain an octane dispersion of purified InP / ZnSe / ZnS quantum dots. The luminescence characteristics of the obtained dispersion were measured, and the results are shown in Table 1.

[0053] [Example 1] (ligand exchange process) 2 ml of the octane dispersion of the green InP / ZnSe / ZnS quantum dots obtained in Synthesis Example 1 (quantum dot concentration 0.100 mmol / ml) and 10 ml of hexadecane were weighed into a 50 ml two-necked eggplant flask. The mixture was heated to 90°C under reduced pressure while stirring and degassed for 30 minutes. After degassing, the mixture was returned to atmospheric pressure with nitrogen gas and heated to 220°C under a nitrogen atmosphere, 4 ml of 3-mercaptopropionic acid was added, and the mixture was held for 10 minutes to obtain InP / ZnSe / ZnS quantum dots in which the ligands were substituted with 3-mercaptopropionic acid. After cooling to 160°C, 40 ml of octane was added and the mixture was cooled to room temperature. The supernatant was removed, 30 ml of hexane was added, and the mixture was stirred, and the supernatant was removed again. This was repeated three times to obtain a solid. The solid was suspended in 5 ml of ethanol, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. (Dispersion process) The collected InP / ZnSe / ZnS quantum dots were dispersed in 3.6 ml of 40% aqueous solution of tetraethylammonium hydroxide, then 6 ml of tetrahydrofuran and 60 ml of 2-propanol were added and stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were dispersed in 1.6 ml of pure water, then 60 ml of 2-propanol was added and stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. This was repeated twice, and the resulting precipitate was dispersed in 10 ml of pure water to obtain an aqueous dispersion of purified InP / ZnSe / ZnS quantum dots. (Surface treatment process) 3 ml of InP / ZnSe / ZnS quantum dot aqueous dispersion (quantum dot concentration 0.020 mmol / ml), 0.082 g of anhydrous zinc chloride, and 5 ml of pure water were weighed into a glass flask with a lid. After reducing the pressure, the flask was returned to atmospheric pressure with nitrogen gas to create a nitrogen atmosphere, and the internal temperature was heated to between 80°C and 100°C while stirring, and then the flask was held for 30 minutes and cooled to room temperature to obtain a surface-treated InP / ZnSe / ZnS quantum dot aqueous dispersion. (Shell formation process) To the obtained surface-treated InP / ZnSe / ZnS quantum dot aqueous dispersion, 0.090 g of anhydrous zinc chloride dissolved in 4.0 ml of pure water and 1.0 ml of 3-mercaptopropionic acid were added. After reducing the pressure, the pressure was returned to atmospheric pressure with nitrogen gas to create a nitrogen atmosphere, and the internal temperature was heated to between 80°C and 100°C while stirring, and after maintaining the temperature for 30 minutes, the mixture was cooled to room temperature to obtain a water-soluble InP / ZnSe / ZnS quantum dot aqueous dispersion. The obtained aqueous dispersion of water-soluble InP / ZnSe / ZnS quantum dots was centrifuged to recover the water-soluble InP / ZnSe / ZnS quantum dots as a precipitate. The recovered precipitate was dispersed in 2.25 ml of pure water and 0.10 ml of a 35% aqueous solution of tetraethylammonium hydroxide, and then centrifuged to remove insoluble impurities, yielding an aqueous dispersion of purified water-soluble InP / ZnSe / ZnS quantum dots. The emission characteristics of the obtained aqueous dispersion were measured, and the results are shown in Table 1. The emission spectrum of the obtained aqueous dispersion is also shown in Figure 1.

[0054] [Example 2] In the ligand exchange step, the same procedure as in Example 1 was carried out, except that the octane dispersion of orange InP / ZnSe / ZnS quantum dots obtained in Synthesis Example 2 was used, to obtain a purified aqueous dispersion of water-soluble InP / ZnSe / ZnS quantum dots. The emission characteristics of the obtained aqueous dispersion were measured, and the results are shown in Table 1. Furthermore, the emission spectrum of the obtained aqueous dispersion is shown in FIG. 2.

[0055] [Example 3] In the ligand exchange step, the same procedure as in Example 1 was carried out, except that the octane dispersion of red InP / ZnSe / ZnS quantum dots obtained in Synthesis Example 3 was used, to obtain an aqueous dispersion of purified water-soluble InP / ZnSe / ZnS quantum dots. The emission characteristics of the aqueous dispersion obtained were measured, and the results are shown in Table 1. Furthermore, the emission spectrum of the aqueous dispersion obtained is shown in FIG. 3.

[0056] [Example 4] In the ligand exchange step, the same operations as in Example 1 were carried out up to the dispersion step, except that the octane dispersion of red InP / ZnSe / ZnS quantum dots obtained in Synthesis Example 3 was used, to obtain an aqueous dispersion of InP / ZnSe / ZnS quantum dots. (Surface treatment process) 0.12g of anhydrous zinc chloride was dissolved in 0.60ml of pure water to obtain an anhydrous zinc chloride aqueous solution. 0.05ml of this anhydrous zinc chloride aqueous solution, 2.0ml of γ-butyrolactone, and 0.03ml of InP / ZnSe / ZnS quantum dot aqueous dispersion (quantum dot concentration 0.025mmol / ml) were weighed into a glass flask with a lid. After reducing the pressure, the pressure was returned to atmospheric pressure using nitrogen gas to create a nitrogen atmosphere, and the internal temperature was heated to between 80°C and 100°C while stirring, and after maintaining the temperature for 30 minutes, the mixture was cooled to room temperature to obtain a surface-treated InP / ZnSe / ZnS quantum dot aqueous dispersion. (Shell formation process) To the obtained surface-treated InP / ZnSe / ZnS quantum dot aqueous dispersion, 0.05 ml of anhydrous zinc chloride solution and 0.02 ml of 3-mercaptopropionic acid were added. After reducing the pressure, the pressure was returned to atmospheric pressure with nitrogen gas to create a nitrogen atmosphere, and the internal temperature was heated to between 190°C and 205°C while stirring, and after maintaining the temperature for 30 minutes, the mixture was cooled to room temperature to obtain a water-soluble InP / ZnSe / ZnS quantum dot aqueous dispersion. The obtained aqueous dispersion of water-soluble InP / ZnSe / ZnS quantum dots was centrifuged to recover the water-soluble InP / ZnSe / ZnS quantum dots as a precipitate. The recovered precipitate was dispersed in 1.0 ml of pure water and 0.1 ml of a 35% aqueous solution of tetraethylammonium hydroxide, and then centrifuged to remove insoluble impurities, yielding an aqueous dispersion of purified water-soluble InP / ZnSe / ZnS quantum dots. The luminescence characteristics of the obtained aqueous dispersion were measured, and the results are shown in Table 1.

[0057] [Example 5] In the ligand exchange step, the same operations as in Example 1 were carried out up to the dispersion step, except that the octane dispersion of orange InP / ZnSe / ZnS quantum dots obtained in Synthesis Example 2 was used, to obtain an aqueous dispersion of InP / ZnSe / ZnS quantum dots. (Surface treatment process) 0.044g of zinc acetate dihydrate was dissolved in 2.0ml of pure water to obtain a zinc acetate aqueous solution. 1.0ml of this zinc acetate aqueous solution, 5.0ml of pure water, and 0.5ml of InP / ZnSe / ZnS quantum dot aqueous dispersion (quantum dot concentration 0.020mmol / ml) were weighed into a glass flask with a lid. After reducing the pressure, the pressure was returned to atmospheric pressure with nitrogen gas to create a nitrogen atmosphere, and the internal temperature was heated to between 80°C and 100°C while stirring, and after maintaining the temperature for 30 minutes, the mixture was cooled to room temperature to obtain a surface-treated InP / ZnSe / ZnS quantum dot aqueous dispersion. (Shell formation process) To the obtained surface-treated InP / ZnSe / ZnS quantum dot aqueous dispersion, 1.0 ml of zinc acetate solution and 0.16 ml of 3-mercaptopropionic acid were added. After reducing the pressure, the pressure was returned to atmospheric pressure with nitrogen gas to create a nitrogen atmosphere, and the internal temperature was heated to between 80°C and 100°C while stirring, and after maintaining the temperature for 30 minutes, the mixture was cooled to room temperature to obtain a water-soluble InP / ZnSe / ZnS quantum dot aqueous dispersion. The obtained aqueous dispersion of water-soluble InP / ZnSe / ZnS quantum dots was centrifuged to recover the water-soluble InP / ZnSe / ZnS quantum dots as a precipitate. The recovered precipitate was dispersed by adding 0.30 ml of pure water and 0.03 ml of a 35% aqueous solution of tetraethylammonium hydroxide, and then centrifuged to remove insoluble impurities, obtaining an aqueous dispersion of purified water-soluble InP / ZnSe / ZnS quantum dots. The luminescence characteristics of the obtained aqueous dispersion were measured, and the results are shown in Table 1.

[0058] [Comparative Example 1] The aqueous dispersion of purified InP / ZnSe / ZnS quantum dots obtained in the dispersion step in Example 1 was used as water-soluble quantum dots, and the luminescence characteristics were measured. The results are shown in Table 1.

[0059] [Comparative Example 2] The aqueous dispersion of purified InP / ZnSe / ZnS quantum dots obtained in the dispersion step in Example 2 was used as water-soluble quantum dots, and the luminescence characteristics were measured. The results are shown in Table 1.

[0060] [Comparative Example 3] The aqueous dispersion of purified InP / ZnSe / ZnS quantum dots obtained in the dispersion step in Example 3 was used as water-soluble quantum dots, and the luminescence characteristics were measured. The results are shown in Table 1.

[0061] [Comparative Example 4] 0.5 ml of the octane dispersion of the orange InP / ZnSe / ZnS quantum dots obtained in Synthesis Example 3 (quantum dot concentration 0.020 mmol / ml) was centrifuged to recover the InP / ZnSe / ZnS quantum dots as a precipitate. The recovered InP / ZnSe / ZnS quantum dots were dispersed in 1 ml of n-hexane to obtain an n-hexane dispersion of InP / ZnSe / ZnS quantum dots (quantum dot concentration 10 mg / ml). 1 ml of the obtained dispersion was placed in a single-neck flask in a nitrogen atmosphere, 1 ml of 28% ammonia water, 0.5 ml of 1-butanol, and 0.25 ml of mercaptopropionic acid were added, and the mixture was heated with stirring to an internal temperature of between 55°C and 65°C. After cooling, 7.5 ml of acetonitrile was added and the mixture was centrifuged. The obtained solid was dispersed in 1.5 ml of pure water to obtain a mixed dispersion of InP / ZnSe / ZnS quantum dots. To the obtained InP / ZnSe / ZnS quantum dot mixed dispersion, 1ml of Zn-mercaptopropionic acid solution was added, which was a mixture of 0.14g of anhydrous zinc chloride, 1ml of mercaptopropionic acid, and 4ml of pure water. The mixture was heated with stirring so that the internal temperature was 70°C to 80°C, and irradiated with ultraviolet light (wavelength 365nm) for 40 minutes while stirring. After stopping the irradiation and 1 hour had passed since the start of stirring, the reaction solution was cooled to room temperature, 4.5ml of acetonitrile was added, and the centrifugal separation was performed twice. The obtained solid was dispersed in 1ml of pure water to obtain a water-soluble InP / ZnSe / ZnS quantum dot aqueous dispersion. The results of measuring the luminescence characteristics of the obtained aqueous dispersion are shown in Table 1.

[0062] [Table 1]

[0063] As shown in Table 1, the quantum dots water-soluble by the manufacturing method of the present invention have the same FWHM as the hydrophobic quantum dots used as the raw material, and it can be seen that the decrease in quantum yield is also suppressed.

Claims

1. a ligand exchange step of adding hydrophilic ligands to the hydrophobic quantum dot dispersion to exchange the ligands bound to the surfaces of the quantum dots with hydrophilic ligands to obtain hydrophilic quantum dots; A dispersing step of dispersing the hydrophilic quantum dots in an aqueous solvent to obtain an aqueous solvent dispersion of the hydrophilic quantum dots; A surface treatment step of adding a surface treatment agent to the aqueous solvent dispersion to perform surface treatment of the hydrophilic quantum dots in the aqueous solvent to obtain an aqueous solvent dispersion of the surface-treated hydrophilic quantum dots; and a shell-forming step of adding a shell-forming agent to the aqueous solvent dispersion of the surface-treated hydrophilic quantum dots to form a shell on the surface of the surface-treated hydrophilic quantum dots to obtain an aqueous solvent dispersion of water-soluble quantum dots; A method for producing a water-soluble quantum dot having the formula:

2. The method for producing water-soluble quantum dots according to claim 1, wherein the quantum dots in the hydrophobic quantum dot dispersion have a core of InP-based quantum dots obtained by reacting at least a phosphorus source and an indium source, and a shell of the quantum dots has a core-shell structure having a coating compound other than InP-based.

3. The shell is made of AlN, AlP, Al 2 O 3 , GaN, GaP, Ga 2 O 3 , SiO 2 3. The method for producing water-soluble quantum dots according to claim 1 or 2, wherein the water-soluble quantum dot is at least one selected from the group consisting of CdS, CdSe, CdSeS, CdTe, CdSeTe, CdTeS, ZnS, ZnSe, ZnSeS, ZnTe, ZnSeTe, ZnTeS, ZnO, ZnOS, ZnSeO and ZnTeO.

4. The hydrophilic ligand used in the ligand exchange step is at least one selected from the group consisting of thiols, amine-containing thiols, amines, alcohols, thiol-containing alcohols, selenols, phosphites, phosphinic acids, phosphonic acids, phosphoric acids, phosphine oxides, phosphine sulfides, phosphine selenides, carboxylic acids, thiol-containing carboxylic acids, thiocarboxylic acids, thionocarboxylic acids, dithiocarboxylic acids, sulfenic acids, sulfinic acids and sulfonic acids. The method for producing water-soluble quantum dots according to claim 1 or 2.

5. The method for producing water-soluble quantum dots according to claim 1 or 2, wherein the aqueous solvent is water.

6. The method for producing water-soluble quantum dots according to claim 1 or 2, wherein the surface treatment agent is a metal halide, a metal carboxylate, a hydrogen halide, a nitrogen halide, a halide of a quaternary ammonium compound or a quaternary phosphonium compound, or a carboxylic acid, a phosphonic acid, a sulfonic acid, or an acid halide thereof.

7. The shell-forming agent is at least one sulfur source selected from thiols, thiol-containing carboxylic acids, thioureas, thiocarbamates, thiocarbonates, thiocarboxylic acids, thionocarboxylic acids, dithiocarboxylic acids, phosphine sulfides, and sulfides of Li, Na, K, Be, Mg, Ca, and Sr, and a mixture of zinc carboxylate, zinc nitrate, zinc sulfate, zinc hypochlorite, zinc chlorite, zinc chlorate, zinc perchlorate, zinc bromate, zinc iodate, zinc carbonate, zinc borate, zinc hypophosphite, zinc phosphite, zinc phosphate, zinc trifluoromethanesulfonate, or zinc halide. The method for producing water-soluble quantum dots according to claim 1 or 2.

8. A water-soluble quantum dot, in which the quantum yield of the water-soluble quantum dot obtained by exchanging ligands bound to the surface of the hydrophobic quantum dot with hydrophilic ligands is greater than 0.8 relative to the quantum yield of the hydrophobic quantum dot.

9. 9. The water-soluble quantum dot according to claim 8, which is a quantum dot having a core-shell structure, the quantum dot having an InP-based quantum dot composed of at least phosphorus and indium elements in the core, and a coating compound other than InP in the shell.

10. The shell is made of AlN, AlP, Al 2 O 3 , GaN, GaP, Ga 2 O 3 , SiO 2 10. The water-soluble quantum dot according to claim 9, which is at least one selected from the group consisting of CdS, CdSe, CdSeS, CdTe, CdSeTe, CdTeS, ZnS, ZnSe, ZnSeS, ZnTe, ZnSeTe, ZnTeS, ZnO, ZnOS, ZnSeO, or ZnTeO.

11. The ligand coordinated to the surface of the water-soluble quantum dot is at least one selected from the group consisting of thiols, amine-containing thiols, amines, alcohols, thiol-containing alcohols, selenols, phosphites, phosphinic acids, phosphonic acids, phosphoric acids, phosphine oxides, phosphine sulfides, phosphine selenides, carboxylic acids, thiol-containing carboxylic acids, thiocarboxylic acids, thionocarboxylic acids, dithiocarboxylic acids, sulfenic acids, sulfinic acids and sulfonic acids. The water-soluble quantum dot according to claim 8 or 9, wherein the ligand is at least one selected from the group consisting of thiols, amine-containing thiols, amines, alcohols, thiol-containing alcohols, selenols, phosphites, phosphinic acids, phosphonic acids, phosphoric acids, phosphine oxides, phosphine sulfides, phosphine selenides, carboxylic acids, thiol-containing carboxylic acids, thiocarboxylic acids, thionocarboxylic acids, dithiocarboxylic acids, sulfenic acids, sulfinic acids and sulfonic acids.

Citation Information

Patent Citations

  • Water-soluble quantum dot, method for producing same, and method for producing quantum dot film

    JP2018538578A

  • Semiconductor structures having polymer and insulator coatings, and compositions and methods for forming same

    JP2020507801A

  • Photoresponsive quantum dot drug delivery system

    JP2020519565A

  • Fluorescent fine particle and method for producing the same, display using the fluorescent fine particle, and fluorescent label or fluorescent reagent of biological substance

    JP2022074714A

  • Quantum dot surface ligand exchange method

    US20200172801A1